Islamic Social Reporting: Viewed from the Aspects of Corporate Governance, Sharia-Based Media Exposure, and Profitability in Indonesia and Its Impact on Company Value - Gusmara, Bayu; Nurlaila, Nurlaila; Inda Fadhila Rahma, Tri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
One way to provide full disclosure in the Islamic context is by applying the ISR. The ISR index is a benchmark for the implementation of Sharia social activities which contains a compilation of CSR standard items set by AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions). The purpose of this research is to explore the impact of Islamic social reporting on firm value. Islamic social reporting refers to disclosing social and environmental information based on Islamic principles. Therefore, it is necessary to analyze the relationship between the strength of corporate governance, media exposure, and Sharia-based profitability with the extent and quality of Islamic social reporting. The research method used is quantitative which uses samples of financial reports from companies listed on the Jakarta Islamic Index (JII) during 2019-2022. The results of the study show that there is an influence of Corporate Governance Strength on Islamic Social Reporting. Then, media exposure to influences of Islamic Social Reporting. It was also found that there was an influence of corporate governance strength, media exposure, and profitability on Islamic social reporting and the influence of Islamic social reporting on company value.